Experimental Study on Freezing Strength of Soil-Concrete Lining Interface in Cold Regions - Zhang Fuping; Shang Jianguo; Geng Wenting; He Pengfei (Geofluids)
The lining of water conveyance canals in cold regions is usually subjected to serious damage, such as spalling, bulging, and fracture, due to the harsh natural environment. The main causes of these types of damage are the normal frost-heaving force and tangential frost-heaving force (adfreeze force) acting on the liner plate. In this study, the adfreeze forces between the foundation soil and liner plate were studied using the direct shear test, considering the effects of the initial water content, test temperature, and compactness. The results show that the increase of the water content, the increase of the temperature, and the decrease of the compactness increased the interfacial peak shear displacement, and they all varied in the range of 0.3–1.6 mm. With the decrease of the initial water content of the soil sample, the increase of the test temperature, and the decrease of the compactness, the peak shear stress decreased significantly with the amplitude between 51 and 87%. The interfacial cohesion decreased significantly with the increase of the initial water content, the increase of the temperature, and the decrease of the compactness. The interfacial friction angle had no apparent variation pattern. At room temperature, the interfacial friction angle decreased significantly with the increase of the water content. When the water content was 30%, the interfacial friction angle was almost lost completely, which can easily lead to the sliding loss of the foundation soil and further damage, such as the instability of the lining.